HLA-G polymorphism and transitional cell carcinoma of the bladder in a Brazilian population - Castelli, Erick da Cruz [UNESP]; Mendes-Junior, C. T.; Camargo, João Lauro Viana de [UNESP]; Donadi, E. A. (Wiley-Blackwell, 2008)
The morphologic appearance and clinical behavior of the human urinary bladder papillary transitional cell carcinoma (TCC) probably result from a complex interaction between carcinogenic insults and host resistance during the patient's life. While the main recognized risk factors are of environmental origin (e.g. smoking), relatively little information exists about the susceptibility to TCC development. The human leukocyte antigen G (HLA-G) molecule plays an important role in immune response regulation and has been implicated in the inhibition of the cytolytic function of natural killer and cytotoxic T cells. Several lines of evidence indicate that HLA-G polymorphisms influence the expression level and production of different HLA-G isoforms. The aim of this study was to explore a possible influence of the HLA-G polymorphism on the susceptibility to urinary bladder TCC development and progression in smokers and nonsmokers Brazilian subjects. The HLA-G locus was found to be associated with susceptibility to TCC development and progression. The G*0104 allelic group (specially the G*010404 allele) and the G*0103 allele were associated with a tobacco-dependent influence on TCC development. The G*0104 group was associated with progression to high-grade tumors, irrespective of smoking habit, while the G*0103 allele was associated to high-grade tumor only in smoking patients. Our results are an evidence that the HLA-G locus itself, or as part of an extended haplotype encompassing this chromosome region (particularly the HLA-A given the high linkage disequilibrium observed between them in this data series), may be associated with TCC susceptibility and tumor progression, suggesting a tobacco-dependent influence of these polymorphisms.
Keywords: bladder; Brazil; HLA-G; polymorphism; tobacco; transitional cell carcinoma